Patient perspectives on current and potential therapies and clinical trial approaches for cocaine use disorder - Maahs, Suzanne; Leclair, Denise; Gomez-Mancilla, Baltazar; Kiluk, Brian D.; Muthusamy, Velusamy Shanmuganathan; Banerjee, Partha S.; Dasgupta, Shyamashree; Waye, Katherine M. (Frontiers in Psychiatry, 2024)
Background Cocaine use disorder (CUD) is characterized by the continued use of cocaine despite serious impacts on life. This study focused on understanding the perspective of individuals with current CUD, individuals in CUD remission, and their supporters regarding current therapies, future therapies, and views on clinical trials for CUD. Methods The online bulletin board (OBB) is a qualitative tool where participants engage in an interactive discussion on a virtual forum. Following completion of a screening questionnaire to determine eligibility, individuals in CUD remission and their supporters logged in to the OBB and responded to questions posed by the moderator. Individuals with current CUD participated in a one-time virtual focus group. Results All individuals with current CUD and 94% of those in CUD remission reported a diagnosis consistent with CUD or substance use disorder during screening. Individuals with current CUD and their supporters were recruited from the United States (US). Individuals in CUD remission were recruited from five countries, including the US. Individuals with current CUD reported hesitation about seeking treatment due to stigma, a lack of privacy, and being labeled as a drug seeker; barriers to therapy included time, cost, and a lack of privacy. Participants wanted a safe therapy to stop cravings and withdrawal symptoms. Seven clinical trial outcomes, including long-term abstinence and craving control, were suggested based on collected insights. Conclusion This study can help inform the design of clinical trials and emphasize the need for effective, safe, and accessible therapies. Recruiting participants will require significant trust building.